Impact of carbon emission reduction on supply chain model with manufacturing decisions and dynamic lead time under uncertain demand - B. Karthick; R. Uthayakumar (Cleaner Logistics and Supply Chain)
Consignment stock policy plays a crucial role in stock management to accomplish more significant benefits for supply chain players. Accordingly, in this research, we developed an inventory model based on the vendor managed inventory and consignment stock agreement by delivering a single item from the single vendor to a single buyer under controllable lead time. Manufacturing industries are a major source of worldwide greenhouse gas emissions. Consumption of larger energy through non-renewable sources increases the use of fossils and coal. Though, this produces more waste and has a negative impact on the environment. In contrast to earlier research, logarithmic investment is employed to control the amount of carbon generated throughout the manufacturing process. The demand rate is treated as a pentagonal fuzzy number to account for the uncertainty. The primary goal of this study is to maximize gross profit with various realistic factors and reduce carbon emissions from the production process. Five numerical experiments, comparison and sensitivity analysis are performed to validate the proposed model. Finally, the benefits of variable pricing and investing in carbon reduction will assist industry managers in effectively managing pricing and inventory strategies to adopt a sustainable supply chain in an uncertain environment.